Machines and Signs A History of the Drawing of Machines - Rovida, Edoardo. (History of Mechanism and Machine Science, 2013)
This volume addresses the cultural, technical and ethical motivations of the history of drawing of machines and its developments step by step. First it treats drawings without any technical character; then the Renaissance with its new forms of drawing; the 18th century, with orthographic projections, immediately used by industry; the 19th century, including the applications of drawing in industry; and the 20th century, with the standardization institutions and the use of the computer. The role of historical drawings and archives in modern design is also examined. This book is of value to all those who are interested in technical drawing, either from an artistic, from a design, or from an engineering point of view.